Efektivitas Berbagai Dosis Larutan Gula merah dan Ragi dalam Botol Plastik Bekas Terhadap Jumlah Nyamuk Terperangkap - Kartiko Nasmudin; Bambang Suwerda; Yamtana Yamtana (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Insecticide application is one method that is often used to control mosquito vector because it canrapidly reduce the population in a short time. However, the use of insecticides can introduce problem because it can pollutes the environment, kills non-target organisms, causes resistance among the vector insect and affects human health. One alternative way to kill mosquitoes is to use mosquito trap that have no negative impact. The purpose of this study was to know the effectiveness of various doses of brown sugar (i.e. 25 gr, 50 gr, and 75 gr) and one gr of yeast in a used plastic bottles as mosquito trap, by conducting a quasi-experimental study which followed post-test group design. The study was located at Pasekan Kidul village, in Balecatur, Gamping, Sleman, since based on the 2013 periodic larvae monitoring data, the village had the lowest percentage of larvae free index, among all service areas of Gamping I Community Health Centre.Data of the study were analyzed statistically by using one way anova at 95 % level of confidence, and it came to conclusion that the dose variation of brown sugar have different effectiveness against the number of mosquitoes trapped (p < 0,001), and 75 grams of brown sugar was found as the most effective dose.